Exploring the Antimicrobial and Antitumor Potentials of Streptomyces sp. AGM12-1 Isolated from Egyptian Soil - Ahmad, Maged S.; El-Gendy, Ahmed O.; Ahmed, Rasha R.; Hassan, Hossam M.; El-Kabbany, Hussein M.; Merdash, Ahmed G. (Frontiers in Microbiology, 2017)
The occurrence of extensive antibiotics resistant bacteria increased the demands for mining out new sources of antimicrobial agents. Actinomycetes, especially Streptomyces sp. have grasped considerable attention worldwide due to production of many useful bioactive metabolites. In the present study, a total of 52 actinomycetes were isolated from agricultural soil samples in Beni-Suef, Egypt. All isolates were characterized based on colony morphology, mycelium coloration, and pigment diffusion. They were screened for their capabilities to show antimicrobial activities against different indicator microorganisms, and only 20 isolates have shown significant antimicrobial activities against at least one of the tested indicator microorganisms. The isolate AGM12-1 was active against all tested microorganisms and showed a marked antitumor activity with IC50 3.3 and 1.1μg/ml against HCT-116 and HepG-2 cell lines respectively. It was genotypically characterized as Streptomyces sp. with the presence of PKS Π biosynthetic gene cluster. Mannitol, ammonium sulfate, pH 7, 2% inoculum size and incubation for 11 days at 30 °C were the optimum conditions that used to maximize the production and hence allowed purification of one active antimicrobial compound to homogeneity using HPLC with a molecular mass of m/z 488.05. NMR structural elucidation showed that this compound was a diketopiperazine derivative.